CAUSES ANDA COMSEQUENCES IN THE PRODUCTION LINE FOR WORKES EXPOSED FOR A CERTAIN TIME IN COLD ENVIRONMENTS - Bragantin da Silva, Fernanda Camila; Rodolpho, Daniela (Revista Interface Tecnológica, 2020)
This article presents the causes and consequences of employees who work in cold rooms and do not use or are not adequately supplied with PPE’s, which can cause serious injuries, for the employee and even for the company. It shows the PPE’s and the descriptions of each item according to NR 6, of which gloves, jacket, balaclava hood, thermal boot and pants, all with thermal lining to withstand the low temperatures of the cold rooms. The working hours in cold rooms, according to article 253 of the CLT, according to NR 36 where the working hours, the necessary breaks and the tolerance for breaks, where companies must have the rotation of employees, preserving health and well-being be the same. The points to evaluate the working conditions being the internal and external noises, the thermal comfort being a measure of prevention to the occupational risks that affect the workers of that area, the biological agents where it must have a correct hygiene of the work places. The results presented and discussions of a sausage factory with employees who do not properly use a specific PPE possibly causing Raynaud’s Phenomenon, concluding that it is essential that every company in the slaughterhouse, slaughterhouses and meat products sector follow the NR 36 and NR 6.